Estágio supervisionado obrigatório leptospirose canina – relato de caso - Veloso, Larissa Soares (Universidade Federal Rural do Semi-Árido, 2021)
This report describes the activities developed during the Mandatory Supervised Internship (ESO), which aimed to add the practice of clinical routine to the theoretical knowledge acquired during the course. This work also aimed to report a case of leptospirosis followed up in the routine of the Veterinary Hospital Quatro Patas, in a two-year-old Border Collie dog, with outdated vaccine and history of travel in various regions of the country. The only clinical manifestation presented was polyuria. Tests such as blood count, serum biochemistry, ultrasound, immunoenzymatic assay (ELISA) for Ehrlichia sp. and Babesia sp. and microscopic serum agglutination test (SAM) for leptospirosis, confirming the clinical suspicion of this disease. The instituted therapy was based on the use of penicillin (amoxicillin) and doxycycline, as recommended in the literature. On the 15th day of treatment, the SAM test was repeated, which showed a negative result. Leptospirosis is a zoonosis of great importance in the context of public health, in view of its cosmopolitan distribution and occurrence favored by environmental conditions existing in regions of tropical and subtropical climate, such as Brazil, and, under certain circumstances, may assume characteristics of outbreaks. It consists of an infectious disease that affects domestic animals, wild animals and humans. In urban areas, dogs (Canis lupus familiar) and the sewer rat (Rattus novergicus) are the main reservoirs of leptospires. From an epidemiological point of view, dogs are of importance in public health because they have close contact with humans and the possibility of being asymptomatic carriers, assuming the condition of a reservoir
Keywords: Zoonose; Cosmopolita; Leptospiras; Cão; Soroaglutinação Microscópica; Zoonosis; Cosmopolitan; Leptospires; Dog; Microscopic Serum Agglutination; CIENCIAS AGRARIAS::MEDICINA VETERINARIA